Challenges of educational leaders’ utilization of educational portal information systems - Al Yahmadi, Hamed Hilal Nasser; Al Husaini, Yousuf Nasser Said (International Journal of Evaluation and Research in Education (IJERE), 2025)
The study aims to determine the challenges that hinder the adoption of educational portal information systems by Omani educational leaders, in order to explore the manner through which their capabilities can be improved. Moreover, the study uses quantitative research through the questionnaire as the main research instrument. The research population consisted of all educational leaders of the educational portal information systems in the Sultanate of Oman. The research sample included 96 individuals from the study population, selected using a convenience sampling method. Moreover, the study findings concluded that the challenges hinder the adoption of educational portal information systems obtained a moderate response degree, whereas the requirements for developing educational portal information systems obtained a very high response degree. Moreover, there were no statistically significant differences in the challenges hinder the adoption of educational portal information systems and the requirements for their development attributed to the variable of gender, years of experience, technological competency, and job position. Lastly, the study recommends the necessity to encourage leaders to participate in workshops and to keep educational leaders continuously updated on the latest improvements of the educational portal is necessary.